Keeping the Nation's House : Domestic Management and the Making of Modern China - Schneider, Helen M. (Book collections on Project MUSE., 2011)
The term home economics often conjures images of girls learning to cook dinner and swaddle dolls in sterile classrooms far removed from the seats of power. Helen Schneider unsettles this assumption by revealing how Chinese women helped to build a nation one family at a time. From the 1920s to the early 1950s, home economists transformed the most fundamental of political spaces - the home - by teaching women to nurture ideal families and manage projects of social reform. Although their discipline came undone after 1949, its legacies of gendered professions and leaders' attempts to shape the domestic rituals of the people lived on.